PENGARUH LAVERAGE, PROFITABILITAS DAN UKURAN PERUSAHAAN TERHADAP KETEPATAN WAKTU PELAPORAN KEUANGAN PERUSAHAAN LQ 45 DI BURSA EFEK INDONESIA - Puryanto Puryanto (BISECER (Business Economic Entrepreneurship), 2020)
One important aspect in financial statements is timeliness because it can maximize information asymmetry. Factors that affect the timeliness of financial reporting leverage, profitability and company size. The formulation of this research problem is the large influence of leverage, profitability and company size on the timeliness of financial reporting. The purpose of this study is to learn more about the leverage, profitability and size of the company against the timeliness of financial reporting.This type of research is associative. The population of this study is LQ 45 companies on the Stock Exchange for the 2014-2018 period, with a sample of 30 companies taken using purposive sampling techniques. Analysis of the data used logistic regression analysis.The results showed that leverage did not have a significant negative effect on the timeliness of financial reporting (sign = 0,162), profitability had a significant negative effect on the timeliness of financial reporting (sign = 0,017), company size showed no significant positive effect on the timeliness of financial reporting (sign = 0,385). The dependent variable can be discussed by the independent variable at 7,2%, the remaining 92,8% is accepted by the variability variable.Investors should be able to choose again in choosing a company that will take place to invest based on the level of growth as an indicator of ability to manage the company.